Silanylidene and Germanylidene Anions: Valence‐Isoelectronic Species to the Well‐Studied Phosphinidene. (6th August 2018) - Siddiqui, Mujahuddin M.; Sinhababu, Soumen; Dutta, Sayan; Kundu, Subrata; Ruth, Paul Niklas; Münch, Annika; Herbst‐Irmer, Regine; Stalke, Dietmar; Koley, Debasis; Roesky, Herbert W.
Abstract: The reduction of TipMCl3 (Tip=2, 4, 6‐triisopropylphenyl) (M=Si, Ge) with KC8 in the presence of cyclic alkyl(amino) carbene (cAAC) afforded the acyclic silanylidene and germanylidene anions in the form of potassium salt [K(cAAC)MTip]2 (M=Si (1 ); Ge (2 )). The silanylidene and germanylidene anions are valence‐isoelectronic to the well‐studied phosphinidene and are a new class of acyclic anions of Group 14. Compounds1 and2 were isolated and well characterized by NMR and single‐crystal X‐ray structure analysis. Furthermore, the structure and bonding of compounds1 and2 was investigated by computational methods.